A Clinical Comparison of Safety and Efficacy in Phacoemulsification with versus without Ophthalmic Viscoelastic Device. (March 2015) - Kugu, Suleyman; Erdogan, Gurkan; Sahin Sevim, M.; Ozerturk, Yusuf
Abstract Purpose: To evaluate in a comparative manner the safety and efficacy of 1.0% sodium-Hyaluronate used during capsulorhexis and intraocular lens (IOL) implantation in phacoemulsification surgery. Materials and Methods: 1.0% sodium-Hyaluronate, which is commonly used as one of the ophthalmic viscoelastic devices, was compared to intraocular irrigating solution, which can bring up these effects. In addition, the effect of both methods on occurring corneal endothelial cell (CEC) loss was investigated. Results: Each group comprised 19 eyes. The mean preoperative CEC density was 2525.68 ± 181.85 in Group H and 2514.16 ± 174.59 in Group V; no statistically significant difference was found between the groups (p > 0.05). Preoperative and postoperative first and twelfth week CEC densities were 2438.21 ± 198.12 (p < 0.001) and 2390.74 ± 202.31, respectively, in group H (p < 0.001). Preoperative and postoperative first and twelfth week CEC densities were 2415.32 ± 197.24 (p < 0.001) and 2353.47 ± 212.69 in group V (p < 0.001). Compared with preoperative values, decrease in CEC density on the postoperative first and twelfth weeks was not statistically significant in either group (p > 0.05). Conclusion: Although it was found that there was no statistically difference in terms of preventing CEC loss between 1.0% sodium-Hyaluronate and the irrigation method during phacoemulsification, it was observed clinically that 1.0% sodium-hyaluronate can make the procedure easy, safer, very helpful, especially for understanding phacoemulsification.